(untitled) (Khairulummah, 2022)
Ahl-e-Suffa were a group of pious people and were the true followers and devotees to Allah and his beloved prophet PBUH. They were the symbol of modesty, leadership, saint, and true guider for the ordinary as well as intellectual class. Kashf-ul-Mahjoob is a matchless masterpiece for those who want to follow the path of Tasawuff. There are golden examples in it for the true followers who want to purify their selves from the wrong wishes and desires to make their soul free from impurities. This research paper will address the personalities who are famous in the history of Islam as ascetics, adorer, veracious, and leader. Their status, position, work, mortification, acquiescence, and excellence will be addressed into the following sections: • Introduction to Suffa and Ahl-e-Suffa • Highness and work of Ahl-e-Suffa • Ahl-e-Suffa as leaders for us in modern times